The Effect of Financial Behavior, Financial Technology, and E-Commerce Adoption on UMKM Income Growth: A Case Study of 'Baku Timba Fest,' Jayapura City - Aprianto La’lang Kuddy; Neni Setiarini; Isma Shalihi Ahlia; Fanny K.T. Sitompul (Syntax Idea)
This study investigates the influence of financial behavior, financial technology, and e-commerce adoption on the income growth of micro, small, and medium enterprises (UMKM) participating in the "Baku Timba Fest" in Jayapura City. Using purposive sampling, data were collected from 30 respondents through questionnaires. Employing a quantitative research method, classical assumption tests and multiple linear regression analyses were conducted. The findings reveal that financial behavior significantly impacts income growth. Although financial technology and e-commerce adoption exhibit a positive relationship with income growth, their effects are not statistically significant. Furthermore, collectively, all three variables significantly influence UMKM income growth. These results highlight the need for targeted strategies to enhance financial behavior and effectively leverage technology for sustainable income growth among UMKM.